Invasive fungal disease in critically ill and Immunocompromised patients - Shazia Shaukat; Irfan Ali Mirza; Rafia Irfan; Mariam Sarwar; Umar khurshid; Wajid Hussain (Journal of the Pakistan Medical Association, 2022)
Objective: To study the frequency and type of invasive fungal disease in critically ill and immunocompromised patients. Method: The prospective, cross-sectional, descriptive study was conducted at the Armed Forces Institute of Pathology, Rawalpindi, Pakistan, from January 2017 to December 2020, and comprised pathological samples from immunocompromised and critically ill patients for fungal culture. Data regarding demographics, comorbidities, results of direct microscopy and fungal culture was recorded. Data was analysed using SPSS 22. Results: Of the 8285 patients specimens, 4722(57%) belonged to males and 3563(43%) to females. The mean age of the patients was 48.32±5.42 years (range: 14-98 years). Out of total 8285, 3465(41.82%) were related to blood, 2640(32%) endobronchial washing, 837(10%) sputum, 623(7.5%) tissue, 332(4%) body fluids, 288(3.5%) bronchoalveoar lavage and 100(1.2%) cerebrospinal fluid. Aspergillus flavus (20.7%) and candida albicans (14.5%) were the two most commonly isolated fungal species. Conclusion: A high index of suspicion for invasive fungal disease should be maintained in immunocompromised and critically ill patients. Key Words: Invasive fungal disease, Critically ill, Immunocompromised, Candida spp., Aspergillus spp.